A case of Hirschsprung's disease underwent surgery in adulthood - Richi Nakatake; Yoshinori Hamada; Hirokazu Miki; Takeshi Shirai; Yusuke Nakamura; Hiroshi Hamada; Morihiko Ishizaki; Masanori Kon (Elsevier, 2016)
Adult Hirschsprung's disease is a rare motor disorder of the gut that is frequently misdiagnosed as refractory constipation. We describe a 30-year-old patient with adult Hirschsprung's disease with a history of chronic constipation requiring daily enema. Barium enema and rectal biopsy showed short segment-type Hirschsprung's disease with a grossly distended sigmoid colon with fecal retention. Staged operations, including the Duhamel-GIA method as a definitive surgery, completely resolved the patient's symptoms. There were no complications by the end of a 7-year follow-up. Adult Hirschsprung's disease should be considered in the differential diagnosis of cases where adult patients present with chronic constipation. Despite technical difficulty of the modified Duhamel-GIA procedure due to chronic fibrous changes of the rectum, it is a feasible surgical option for treating cases of adult Hirschsprung's disease.